2012
DOI: 10.1371/journal.pone.0038150
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis on Pharmacogenetics of Platinum-Based Chemotherapy in Non Small Cell Lung Cancer (NSCLC) Patients

Abstract: AimTo determine the pharmacogenetics of platinum-based chemotherapy in Non Small Cell Lung Cancer (NSCLC) patients.MethodsPublications were selected from PubMed, Cochrane Library and ISI Web of Knowledge. A meta-analysis was conducted to determine the association between genetic polymorphisms and platinum-based chemotherapy by checking odds ratio (OR) and 95% confidence interval (CI).ResultsData were extracted from 24 publications, which included 11 polymorphisms in 8 genes for meta-analysis. MDR1 C3435T (OR =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 66 publications
(61 reference statements)
2
34
0
Order By: Relevance
“…Our previous studies showed that genetic polymorphisms were useful clinical markers for chemotherapy response and toxicity prediction in lung cancer patients [9, 2729]. To investigate the relationship between MMR pathway genetic polymorphisms and platinum-induced toxicity, we evaluated 6 MMR genes ( MLH1 , MSH2 , MSH3 , MSH4 , MSH5 , and MSH6 ) in Chinese NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that genetic polymorphisms were useful clinical markers for chemotherapy response and toxicity prediction in lung cancer patients [9, 2729]. To investigate the relationship between MMR pathway genetic polymorphisms and platinum-induced toxicity, we evaluated 6 MMR genes ( MLH1 , MSH2 , MSH3 , MSH4 , MSH5 , and MSH6 ) in Chinese NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…There were two meta-analyses which reported the inconsistent results for evaluating the associations between GSTP1 and GSTM1 polymorphisms and response to platinum-based chemotherapy in lung cancer 17, 40 . These two meta-analyses have not enrolled update studies and just analyzed a few studies, and thus may have biased conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…5 There is accumulating evidence to support the hypothesis that genetic polymorphisms alter drug response and survival. [6][7][8][9][10][11] Cytochrome P450 (CYP) is a superfamily of phase I oxidation enzymes, the first 3 families of which metabolize xenobiotics such as environmental carcinogens and various drugs (Table 1) including antineoplastic drugs (Table 2). [12][13][14][15][16] They are also involved in drug resistance.…”
Section: Introductionmentioning
confidence: 99%